PERAN KEPEMIMPINAN TRANSFORMASIONAL MEMODERASI PENGARUH KOMPETENSI PROFESIONAL DAN KEPUASAN HIDUP TERHADAP KINERJA GURU (Studi Kasus Pada SMA Negeri Di Kecamatan Pati Kabupaten Pati) - Dewi Ayun, 12.52.02.0191; Srimindarti, Ceacilia (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze whether transformational leadership moderates the influence of professional competence and life satisfaction on teachersâ performance of senior high school in District Pati of Pati regency.The results showed that; professional competence and life satisfaction positive and significant impact on teacher performance. Transformational leadership is also proved able to moderate the influence of professional competence and life satisfaction on teacher performance. Keywords: professional competence, life satisfaction, transformational leadership, teachersâ performance